INFLUENCE OF THE VOLUME OF INDUSTRIAL PRODUCTION IN UZBEKISTAN ON THE IMPORT TREND - Sabirov Khasan Nusratovich; Akbarova Asidaxon (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
The main goal of the scientific research is to study the interaction of industrial production in Uzbekistan with the volume of imports, and statistical data for the period of 2010-2021 were used in the research. First, a summary of the scientific articles on the topic was shown, and an econometric model was used to conduct the research. During the research, a multi-factor correlation-regression analysis was conducted and a model was created. Fisher test and Durbin-Watson test were used. In the results of scientific research, it was found that there is no connection between industrial production and import. At the end of the article, proposals and conclusions are given on the rapid development of industrial production and reduction of imports.